A educação profissional sob o signo da qualidade: um jogo de duplo sentido - Paulino, Antonio George Lopes (2002)
This dissertation focus on the professional education field and the changes that have been made in the work area. The globalism and productive restructuralism phenomena constitutes a socioeconomical scenery characterized for an intensive competitivity ofthe market that redefines administrative and organizational paradigms in function of the triad: productivity, quality and excellency. The quality paradigm from japanese origim spreads itself as strategical form, reaching the flexible accumulation logic, the production and reproduction horizon of the meanings that hold the relationship between education and work. A mix of market concepts - used as the unique neoliberalism thinking - with categories ofthe social interation field, produces a complex and polissemic net, meaningful groups many times paradoxal. The Serviço Nacional de Aprendizagem Industrial - SENAI institution that assumes in ao emblematic way the reproduction ofthe quality sign in education, has been analyzed in this research work, with interpretative abordage searches to understand the different representation that reveals throught the dissemination of the institutional speach and the reception of this rhetoric for individuais who live directly the praxis of the learning-teaching process, holding as an investigation field the Centro Modelo de Educação Profissional Antônio Urbano de Almeida, CEMEP AUA, a professional school of SENAI, Regional Department of Ceara.